GREEN COFFEE EXTRACT INDUCES ACTIVATION MARKERS IN J774.1 MACROPHAGES AND PROTECTS THEM FROM DOXORUBICIN INDUCED APOPTOSIS - SRIVIDYA MALKAPURAM; SWAMINI TARAN; KRISHNAN VENKATARAMAN; LAKSHMAN RAJAGOPALAN (International Journal of Pharma and Bio Sciences, 2016)
Green Coffee Extract (GCE) is a popular health supplement known for its anti-obesity & anti-diabetic effects. Here we tested GCE for its capacity to activate J774.1 mouse macrophages and protect against Doxorubicin induced apoptosis. J774.1 cells treated for 24 h with 100 and 500 µg/ml GCE showed increased production of IL-6, TNF-α and nitric oxide (NO) in a dose dependent manner. GCE upregulated production of these molecules by inducing transcription of the IL-6, TNF-α and iNOS genes. In addition, GCE was able to restore viability of J774.1 cells treated with Doxorubicin. Pre-treatment of cells with GCE for 1 h abrogated Dox induced loss of cell viability. While Dox robustly induced caspase 3/7 activity within 6 h of treatment, pre-treatment with GCE for 1 h was enough to attenuate this induction. The results we report here suggest that GCE activates J774.1 macrophages and is cytoprotective against Dox induced apoptosis.